Catalytic enantioselective synthesis of atropisomeric biaryls by a cation-directed O-alkylation - Jolliffe, J; Armstrong, R; Smith, M (Nature Publishing Group, 2017)
Axially chiral biaryls, as exemplified by 1,1’-bi-2-naphthol (BINOL), are key components of catalysts, natural products and medicines. These materials are synthesized conventionally in enantioenriched form through metal- mediated cross coupling, de novo construction of an aromatic ring, point-to-axial chirality transfer or an atropselective transformation of an existing biaryl. Here, we report a highly enantioselective organocatalytic method for the synthesis of atropisomeric biaryls by a cation-directed O-alkylation. Treatment of racemic 1-aryl-2- tetralones with a chiral quinidine-derived ammonium salt under basic conditions in the presence of an alkylating agent leads to atropselective O-alkylation with e.r. up to 98:2. Oxidation with DDQ gives access to C2-symmetric and non-symmetric BINOL derivatives without compromising e.r. We propose that the chiral ammonium counterion differentiates between rapidly equilibrating atropisomeric enolates, leading to highly atropselective O- alkylation. This dynamic kinetic resolution process offers a general approach to the synthesis of enantioenriched atropisomeric materials.